Biochemical Messengers - Hardie, D. author. aut Link
X, 311 p.
Keywords: The central theme of this book is that systems of cell-cell signalling via nerves, hormones, local mediators and growth factors are not distinct phenomena, but branches of one general mechanism. These topics therefore can and should be discussed in an integrated manner, and the division of cell signalling studies into separate pigeonholes such as neuroscience, endocrinology or cancer biology is unnecessary, if not counterproductive. I also believe it to be unfortunate that there is not a collective term to describe neurotransmitters, hormones, local mediators and growth factors, other than clumsy phrases such as "extracellular signal molecule". The lack of a short and distinctive word for these entities genuinely hampers people from thinking about them in an integrated way. Having decided that it was presumptuous to invent a new term, I have chosen in this book the term first messenger to cover all types of extracellular signal molecule, because of the widespread acceptance of the term second messenger to represent the intracellular signal molecules that are produced in response to many of them. I have given the book the title "biochemical messengers", which is a global term to cover both first and second messengers. The impetus for writing the book came, as must often be the case, when I had to put together a course on cell-cell signalling for biochemistry students at the University of Dundee.